A Genetic System for the Thermophilic Acetogenic Bacterium Thermoanaerobacter kivui - Basen, Mirko (Appl Environ Microbiol, 2018)
Thermoanaerobacter kivui is one of the very few thermophilic acetogenic microorganisms. It grows optimally at 66°C on sugars but also lithotrophically with H(2) + CO(2) or with CO, producing acetate as the major product. While a genome-derived model of acetogenesis has been developed, only a few physiological or biochemical experiments regarding the function of important enzymes in carbon and energy metabolism have been carried out. To address this issue, we developed a method for targeted markerless gene deletions and for integration of genes into the genome of T. kivui. The strain naturally took up plasmid DNA in the exponential growth phase, with a transformation frequency of up to 3.9 × 10(−6). A nonreplicating plasmid and selection with 5-fluoroorotate was used to delete the gene encoding the orotate phosphoribosyltransferase (pyrE), resulting in a ΔpyrE uracil-auxotrophic strain, TKV002. Reintroduction of pyrE on a plasmid or insertion of pyrE into different loci within the genome restored growth without uracil. We subsequently studied fructose metabolism in T. kivui. The gene fruK (TKV_c23150) encoding 1-phosphofructosekinase (1-PFK) was deleted, using pyrE as a selective marker via two single homologous recombination events. The resulting ΔfruK strain, TKV003, did not grow on fructose; however, growth on glucose (or on mannose) was unaffected. The combination of pyrE as a selective marker and the natural competence of the strain for DNA uptake will be the basis for future studies on CO(2) reduction and energy conservation and their regulation in this thermophilic acetogenic bacterium. IMPORTANCE Acetogenic bacteria are currently the focus of research toward biotechnological applications due to their potential for de novo synthesis of carbon compounds such as acetate, butyrate, or ethanol from H(2) + CO(2) or from synthesis gas. Based on available genome sequences and on biochemical experiments, acetogens differ in their energy metabolism. Thus, there is an urgent need to understand the carbon and electron flows through the Wood–Ljungdahl pathway and their links to energy conservation, which requires genetic manipulations such as deletion or overexpression of genes encoding putative key enzymes. Unfortunately, genetic systems have been reported for only a few acetogenic bacteria. Here, we demonstrate proof of concept for the genetic modification of the thermophilic acetogenic species Thermoanaerobacter kivui. The genetic system will be used to study genes involved in biosynthesis and energy metabolism, and may further be applied to metabolically engineer T. kivui to produce fuels and chemicals.